Family Businesses as a Determinant of Region’s Sustainable Development - Zygmunt, Aleksandra (Regional Barometer. Analyses & Prognoses, 2015)
The main aim of the article is to highlight the significance of family businesses in regional development balancing. At first, the special attention was put on issues related to the sustainable development of regions. In this respect, it has been indicated key assumptions of sustainable development policy according to the European Union, and Polish actions in this area included in the National Development Strategy 2020, the National Regional Development Strategy 2010–2020 and the Long-term National Development Strategy. Next, it was made considerations concentrated on the determinants of regional development balancing. Particular attention was focused on endogenous determinants, which characterize important role in region’s sustainable development. Among them special place constitute the region’s competitiveness. The results of the literature research indicate that in this area a key role may play family businesses due to their specific nature and importance in the economy. As a result, family businesses should be regarded as an essential endogenous component of region’s sustainable development.